EVOLUTION OF THE COMPONENTS OF SPORTSMANSHIP AND AGGRESSION IN TERMS OF WATER POLO PLAYER POSITIONS - Dávid, Barbara; Csukonyi, Csilla; Ocsenás, Dorottya; Kardos, Sándor (Stadium - Hungarian Journal of Sport Sciences, 2021)
Two commonly used constructs in sport psychology researches are aggression and sportsmanship. In the present research, we attempted to assess the correlations between these two phenomena among male water polo players. The main objective was to explore the differences in aggression in the sport-specific positions of water polo in different aspects - physique, age, etc. - considered. Furthermore, the research sought to demonstrate the inverse relationship between aggression and sportsmanship in a water polo sample. To access these constructs in our research besides the Buss-Perry Aggression Questionnaire and the Sportsmanship Attitude Scale a self-formulated water polo specific questionnaire was used, which intended to measure the aggression in the water during water polo matches. From the results, it can be seen that, according to our sample, both the trait aggression of the players and the role determined by their positions in the game play a decisive role when it comes to the aggression of an athlete. Moreover, the results obtained for water polo players also proved that sportsmanship and aggression are two contradictory constructs.